The Elite Cassava Genotypes with High Yield and Stability in Diverse Environmental Conditions of Ethiopia - Atnafua, B.; Tesfaye, T.; Asfaw, K.; Tewodros, M.; Getachew, E.; Neim, . (Current Topics in Agricultural Sciences Vol. 2, 2021)
Cassava is grown mainly in South region of Ethiopia. However, it shows expansion to northern, eastern and western parts of the country. In this study, evaluation of eleven cassava germplasms promoted from previous preliminary work was done at different agro-climatic conditions. The list of cassava genotypes used in the study were 1038, 869, Umbure, M94/0117, 1554, 1630, 1708, M94/0125, 196/624, Kello (standard check) and Local farmers variety. These were planted in two growing seasons of 2015/2017 and 2017/2019. The experiment was conducted at four different locations namely Hawassa, Dilla, Areka and Jima. The treatments were arranged in randomized complete block design and replicated three times. The statistical analysis was computed using two computer statistical software packages; Gen Stat and SAS (1999). SAS software was used to compute analysis of variance. Gen Stat computer software was used to determine the stability of the genotypes across different locations. The result showed that presence of significant difference among cassava genotypes due to root yield. Based on genotypic stability index, the cassava genotypes 1708 and M94/125 selected as best varieties due to their high stability and yield performance in various environmental conditions. The correlation coefficient indicated association among different agronomic trait. Regarding to this, total root yield of cassava was highly significant and positively correlated with stand count (r=0.90), storage root length (r=0.86) rather highly significant and negative correlation was found between total root yield to above ground biomass weight (r= -0.74), plant height (r=-0.77) and storage root girth (r= -0.04).